Hypopituitarism is associated with lower oxytocin concentrations and reduced empathic ability - Daughters, Katie (Endocrine, 2017)
PURPOSE: Central diabetes insipidus is characterised by arginine vasopressin deficiency. Oxytocin is structurally related to vasopressin and is synthesised in the same hypothalamic nuclei, thus we hypothesised that patients with acquired central diabetes insipidus and anterior hypopituitarism would display an oxytocin deficiency. Moreover, psychological research has demonstrated that oxytocin influences social and emotional behaviours, particularly empathic behaviour. We therefore further hypothesised that central diabetes insipidus patients would perform worse on empathy-related tasks, compared to age-matched and gender-matched clinical control (clinical control-isolated anterior hypopituitarism) and healthy control groups. METHOD: Fifty-six participants (age 46.54 ± 16.30 yrs; central diabetes insipidus: n = 20, 8 males; clinical control: n = 15, 6 males; healthy control: n = 20, 7 males) provided two saliva samples which were analysed for oxytocin and completed two empathy tasks. RESULTS: Hypopituitary patients (both central diabetes insipidus and clinical control groups) had significantly lower oxytocin concentrations compared to healthy control participants. Hypopituitary patients also performed significantly worse on both the reading the mind in the eyes task and the facial expression recognition task compared to healthy control participants. Regression analyses further revealed that central diabetes insipidus patients’ oxytocin concentrations significantly predicted their performance on easy items of the reading the mind in the eyes task. CONCLUSIONS: Hypopituitarism may therefore be associated with reduced oxytocin concentrations and impaired empathic ability. While further studies are needed to replicate these findings, our data suggest that oxytocin replacement may offer a therapeutic approach to improve psychological well-being in patients with hypopituitarism.